Cr(VI) reduction in aqueous solutions by using pyrite - Erdem, Mehmet; Tümen, Fikret (My University, 1996)
In this study, the effects of the amount of acid, pyrite dosage, contact time, initial Cr(VI) concentration, temperature and pyrite particle size on the Cr(VI) reduction in the aqueous solution by using pyrite were investigated. The Cr(VI) in the concentration range of 80-150 mg/l has been effectively reduced within a contact period of 75 min with the pyrite at the 10 g/l dosage and -270 mesh particle size in the solution containing twice as much of the stoichiometric amount of H2SO4. Results have shown that pyrite is an effective reductant but its reduction capacity is low compared to theoretical calculations.:.
Pirit kullanilarak sulu çözeltilerde CR(VI) i?ndirgenmesi
Keywords: Chromium; Cr(VI) reduction; Heavy metal removal; Pyrite